Enhancer and promoter elements directing activation and glucocorticoid repression of the alpha 1-fetoprotein gene in hepatocytes. - Guertin, M (1988)
Mutations were introduced in 7 kilobases of 5'-flanking rat alpha 1-fetoprotein (AFP) genomic DNA, linked to the chloramphenicol acetyltransferase gene. AFP promoter activity and its repression by a glucocorticoid hormone were assessed by stable and transient expression assays. Stable transfection assays were more sensitive and accurate than transient expression assays in a Morris 7777 rat hepatoma recipient (Hepa7.6), selected for its strong AFP repression by dexamethasone. The segment of DNA encompassing a hepatocyte-constitutive chromatin DNase I-hypersensitive site at -3.7 kilobases and a liver developmental stage-specific site at -2.5 kilobases contains interacting enhancer elements sufficient for high AFP promoter activity in Hepa7.6 or HepG2 cells. Deletions and point mutations define an upstream promoter domain of AFP gene activation, operating with at least three distinct promoter-activating elements, PEI at -65 base pairs, PEII at -120 base pairs, and DE at -160 base pairs. PEI and PEII share homologies with albumin promoter sequences, PEII is a near-consensus nuclear factor I recognition sequence, and DE overlaps a glucocorticoid receptor recognition sequence. An element conferring glucocorticoid repression of AFP gene activity is located in the upstream AFP promoter domain. Receptor-binding assays indicate that this element is the glucocorticoid receptor recognition sequence which overlaps with promoter-activating element DE.